Incidence of testicular tumor subtypes according to the updated WHO classification, North Rhine‐Westphalia, Germany, 2008–2013. (21st December 2018) - Stang, A.; Rusner, C.; Trabert, B.; Oosterhuis, J. W.; McGlynn, K. A.; Heidinger, O.
Abstract: Background: In 2016, the WHO introduced an updated classification for testicular tumors. The application of this updated classification to cancer registry data requires some recoding of tumors. Objectives: The aim of this study was to provide up‐to‐date population‐based incidence estimates of subtypes of testicular germ cell tumors (TGCT) according to the updated classification. Material and methods: We reviewed 2251 pathology reports (42.9%) out of 5252 testicular tumors at the cancer registry of North Rhine‐Westphalia for the years 2008–2013. We used population counts to estimate age‐standardized incidence rates per million person‐years (EUROSTAT revised European Standard Population). Results: The application of the updated WHO classification resulted in a recoding of 8.9% of all testicular tumors. While the recodings have no influence on the incidence of seminomatous and non‐seminomatous TGCTs that include mixed TGCTs, they influence the incidence of individual histological types of seminomatous and non‐seminomatous TGCTs. Among the 4935 testicular germ cell tumors (TGCT), 23.7% were mixed TGCTs. Overall, 46.9% of all mixed TGCTs included seminoma and age‐standardized incidence rates were highest for the combination seminoma plus embryonal carcinoma (5.9 per million person‐years) and embryonal carcinoma plus teratoma (4.9 per million person‐years). The median age at diagnosis was higher for mixed TGCTs including seminoma (31 years) than those that did not include seminoma (28 years). Discussion and conclusions: Population‐based incidence time trends for seminomatous and non‐seminomatous TGCTs that include mixed TGCTs are not distorted by the introduction of the WHO update. Trend distortions can only be expected if time trends of individual histological subtypes of the seminomatous and non‐seminomatous TGCTs are examined.